The Relationship Between Serum Levels Of CA- 125 and Interleukin -6 with the Degree of Differentiation in Ovarian Neoplasms - Rajput, Minakshi; Kulkarni, C. V.; Yadav, Ashok; Sharma, Sachin; Dhakad, Vinod (Annals of Pathology and Laboratory Medicine, 2019)
Background: To study the serological correlation between serum levels of CA -125 and IL-6 with various histo morphological features of ovarian neoplasm. Methods: Prospective study of two year duration from 2016 to 2018.Total of 40 women presented clinically with pelvic mass lesion were included. These patients undergoing concomitant serological analysis of CA -125 and IL-6. In each case, age, parity, marital life, radiological finding, histological type, degree of differentiation, extra ovarian tissues involvement was determined. Result: Most of the ovarian neoplasm belongs to benign category 19/40 (47.5%) then malignant tumors 15/40 (37.5%). Surface epithelial tumours (80%) were common histopathological findings with raised CA-125 and Interleukin-6 levels. Most of the patient present with abdominal pain in their late reproductive age group (41-60 years). There is significant correlation ( p-value=.000) in rise of levels of CA-125 and Interleukin-6 levels in patients with benign and malignant ovarian lesion. Levels of both the biomarkers are near normal levels in benign cases and levels were raised in malignant cases. Conclusion: Amongst the ovarian neoplasm benign tumor were more common than malignant with predominance histological type is surface epithelial tumors. Serum levels of CA –125 and IL-6 were associated with histological grade in primary ovarian neoplasms, especially in high-grade malignant tumors, suggesting that high serological levels of these biomarkers are associated with lesions of more aggressive biological behavior.